Implementasi Case Method Untuk Meningkatkan Kompetensi Guru - Andri Rahadyan; Indra Kurniawan; Lin Suciani Astuti; Dona Katarina; Muslihatul Hidayah; Vini Rizqi; Andreas Adi Trinoto (Lembaga Pengembangan Kinerja Dosen, 2024)
Interactive learning articulating storylines based on the case method developed can improve students' solving abilities. This community service activity aims to increase the understanding of Primagama Bekasi Homeschooling teachers regarding the implementation of the case method in learning to improve teacher competency. Implementation of community service is carried out through several stages such as assessment, planning and development, implementation (socialization), and evaluation. The number of participants was around 20 Bekasi HSPG teachers. Based on these results, information was obtained that this activity was very relevant to the participants' needs. This activity increases knowledge and skills about implementing the case method in learning. If it is made in the form of a percentage increase from the initial ability of 35%, after socialization, those who understand will be more than 75%.